Features of the international student migration from the Republic of Uzbekistan to the Russian Federation (on the example of the Northern (Arctic) Federal University, 2009-2024) - P. S. Golomidova (RUDN journal of Sociology)
The article considers the features of formation and development of regional migration flows on the example of the international student migration from Uzbekistan to the Lomonosov Northern (Arctic) Federal University (NArFU, Arkhangelsk) in 2009-2024. The author focuses on the transition from the flow initiation phase to the stage when the student flow becomes self-sustaining and on the role of migration networks and migration industry in this flow formation and development. The article is based on the statistical data (admission of international students in the NArFU), a survey and semi-formalized interviews with NArFU students from Uzbekistan, expert interviews with representatives of the migration industry, and the author’s participant observation within her professional activity. Four stages of the regional student migration development were identified, which are heterogeneous in features and social organization. The migration industry played a key role in ensuring the growth of the migration flow from 2013 to 2017, while in 2020-2021, the stability of the flow was largely ensured by migration networks, which is confirmed by its stability under negative macro-factors (pandemic) and by the development of regional sub-flows from Namangan and Tashkent Regions. The development of migration networks and admission of new students from Uzbekistan was also strongly supported by students who successfully had adapted to the new learning and cultural environment, accumulated social capital in the host community and at the same time maintained social ties in the sending community. The author applied Hein de Haas’s concept of the internal dynamics of migration flows to prove that the comprehensive activities of the university to integrate into the migration industry, including support measures for international students within the university, is a prerequisite for the successful adaptation of academic migrants, which contributes to the further development of network migration.